PELAKSANAAN RETRIBUSI JASA USAHA DI UPTD LABORATORIUM DINAS LINGKUNGAN HIDUP KOTA PADANG - Meita Lefi Kurnia dan Sarmen (Normative Jurnal Ilmiah Hukum, 2020)
Kota Padang The capital of West Sumatra Province has many business entities, such as the cement, rubber, wood, restaurant, warehouse and many other industries, which can have an impact on environmental quality. in responding to that matter, the City Government of Padang provided an environmental quality testing laboratory to run the Padang City Regulation No. 12 of 2011 concerning Business Service Levies, the problem here is how to implement business service levies at the UPTD Laboratory of the Environmental Service Office of the City of Padang, to answer the above questions The author conducts research using the method of legal research of sociological juridical or legal research that focuses on field research to obtain primary data, besides that it also conducts research on secondary data obtained from primary legal materials, secondary legal materials and tertiary legal materials. the nature of this research is descriptive which illustrates broadly the Implementation of Business Service Levies in the UPTD Laboratory of the Padang City Environment Agency. From primary data and secondary data collected then the data is processed by editing, coding, tabulating, after the data is processed then analyzed qualitatively to get conclusions. based on research by the author, it can be concluded that the implementation of Business Services Levies in the UPTD Laboratory of the Padang City Environment Agency, where the quality assurance of the results of the test is very accurate and reliable because the UPTD Laboratory of the Padang City Environment Agency has been accredited by the National Accreditation Committee (KAN) and has fulfilled the National standard based on ISO / IEC 17025 the latest edition of the general requirements of the competence of testing and calibration laboratories.